Strategi UMKM dalam Menghadapi Disrupsi Digital: Studi Literatur pada Transformasi Ekonomi di Indonesia - Riza Indriani; Afifah Nida Suhailah Boru Dalimunthe; Farel Akbar Aditya Saragih; Fikri Al Kautsar; Ovan Krisadelman Zebua; Kevin Valensius Siahaan; Cipta Kurnia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study addresses the growing challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia amid rapid digital disruption, which has reshaped market structures and consumer behavior. The research aims to identify adaptive strategies adopted by MSMEs and to examine the key supporting and inhibiting factors in their digital transformation process. A qualitative descriptive approach was employed through a structured literature review of academic journals, books, and institutional reports published between 2015 and 2023. The selected literature was analyzed using thematic categorization to identify recurring patterns and research gaps. The findings reveal that MSMEs respond to digital disruption by adopting e-commerce platforms, implementing digital marketing practices, engaging in digital ecosystem collaborations, and developing product and service innovations. The study also highlights that successful transformation is influenced by government support, digital infrastructure availability, digital literacy, and access to financial technology. However, limitations such as low digital capability, restricted capital, human resource constraints, and uneven infrastructure remain significant barriers. This study contributes by synthesizing fragmented findings into a comprehensive framework of MSME digital adaptation in Indonesia.